2017
DOI: 10.5694/mja16.00833
|View full text |Cite
|
Sign up to set email alerts
|

Emerging infectious disease agents and blood safety in Australia: spotlight on Zika virus

Abstract: Summary   Emerging infectious diseases (EIDs) are infectious diseases whose incidence has increased in humans in the past 20 years or could increase in the near future. EID agents may represent a threat to blood safety if they infect humans, cause a clinically significant illness, include an asymptomatic blood phase in the course of infection, and are transmissible by transfusion. EID agents are typically not well characterised, but there is a consensus that we can expect ongoing outbreaks. Strategies to mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We thank Wiwanitkit for the comments on our review 1 . We agree that the absence of reported transfusion‐transmission of Zika virus (ZIKV) in Australia is not definitive evidence that this type of ZIKV transmission has not occurred or will not occur in the future.…”
mentioning
confidence: 93%
“…We thank Wiwanitkit for the comments on our review 1 . We agree that the absence of reported transfusion‐transmission of Zika virus (ZIKV) in Australia is not definitive evidence that this type of ZIKV transmission has not occurred or will not occur in the future.…”
mentioning
confidence: 93%
“…However, there are opposite attitudes towards mandating routine screening of ZIKV in blood collections because it is time-consuming and costly. Some consider that the TT risk of Zika in their country is low [15, 16], and there is no urgent need to introduce universal screening of donated blood for ZIKV [17]. On the other hand, some studies mentioned that present measures were not effective enough to prevent transfusion of ZIKV RNA-reactive blood products, and ZIKV NAT should be used [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…I found the article by Kiely and colleagues 1 very interesting. The authors concluded that “it should be noted that a relatively small number of imported ZIKV [Zika virus] infections have been reported in Australia, there have been no reported cases of local ZIKV transmission, and the geographical distribution of the potential ZIKV mosquito vector in Australia ( Aedes aegypti ) is limited to northern Queensland,” and that “at present, ZIKV represents a low risk to blood safety in Australia.” 1 …”
mentioning
confidence: 97%